Designing a Supply Chain Visibility Information System for the Manufacturing Industry - Liam Murphy (IPTEK The Journal of Engineering, 2023)
This paper evaluates the design and success of an Information System developed in a just-in-time UK manufacturer to combat the lack of visibility and financial impact caused by supply chain disruptions related to extreme weather and traffic events. An information system design is first presented through the use of leading academic models, with a subsequent evaluation of perceived success via 4 employee interviews within the UK manufacturer. The DeLone and McLean model Multi-Perspective Evaluation model is then used to present the interviewees responses. This paper finds the newly introduced IS to be a partial success in meeting project objectives via the reduction of incident response time by 30 minutes per incident, and the centralization of key data points. This paper contributes to literature through the provision of framework and learnings for other organizations to build and act upon, in the aims of reducing their own supply chain disruption due to extreme weather and traffic events.